Incidencia de la comunicación organizacional interna en el clima laboral de los servidores públicos del Gobierno Autónomo Descentralizado Municipal de Portoviejo - Muñoz Zambrano, Mayra Inés (2023)
The present study was developed with the objective of evaluating the incidence of internal organizational communication in the work environment in public servants of the Municipal Decentralized Autonomous Government of Portoviejo, to give more support to the investigation, methods such as inductive, deductive, analytical - Synthetic, Pearson's correlation and types of research such as bibliographic and field, on the other hand, to provide a greater focus to the inquiry, an interview was conducted with the Director of Human Talent and a survey of the servers that work in the GAD, where It was possible to know the current state of the work environment and the internal organizational communication of all the personnel who carry out their functions in the different dependencies of the institution. Therefore, it was possible to detect that public servants do not have a suitable space, deficiency in internal communication between workers, and that after the 2016 earthquake communication was maintained. In the same way, the survey indicates that it is important to improve communication, teamwork, the work environment, the control process, decision-making, because they are basic when performing any function and thus being able to execute efficiently and effectively each task. Finally, the proposal to design a plan is born to contribute to the improvement of internal communication in such a way that the institution can show the weaknesses and manage to implement a more effective communication plan, in which the productivity of the institution increases.